Killer ChatGPT prompts harness the power of AI for success and profit - Hart-Davis, Guy (John Wiley & Sons, Inc, 2023)
"Unlock the full capabilities of ChatGPT at work, at home, and in your day-to-day. By now, you've heard of ChatGPT and its incredible potential. You may even have tried to use it a few times just to see it in action for yourself. But have you ever wondered what ChatGPT is truly capable of? Killer ChatGPT Prompts: Harness the Power of AI for Success and Profit will show you the true power of Large Language Models (LLMs) like ChatGPT. In the book, veteran IT educator and trusted author Guy Hart-Davis shows you the exact prompts he's discovered to unlock a huge variety of expert business writing, like emails and proposals, data analysis use cases, lesson plans, information exchange scripts, and more!"--Amazon.com.
Includes index. - Description based on online resource; title from digital title page (viewed on September 29, 2023)
Keywords: ChatGPT; Artificial intelligence; Chatbots; Natural language generation (Computer science); Génération automatique de texte; Intelligence artificielle; artificial intelligence